Tumor necrosis factor-α in human American tegumentary leishmaniasis - Alda Maria Da-Cruz; Márcia Pereira de Oliveira; Paula Mello De Luca; Sergio CF Mendonça; Sergio G Coutinho (Memorias do Instituto Oswaldo Cruz, 1996)
Tumor necrosis factor-alpha (TNF-α) is a cytokine produced by activated macrophages and other cells. In order to verify whether the serum levels of TNF-α in American tegumentary leishmaniasis patients are associated with the process of cure or aggravation of the disease, 41 patients were studied: 26 cases of cutaneous leishmaniasis (CL) and 15 of mucocutaneous leishmaniasis (MCL). During active disease the serum levels of TNF-α of MCL patients were significantly higher than those of CL patients and control subjects (healthy individuals and cutaneous lesions from other etiologies). The MCL patients had serum titers of TNF-α significantly lower at the end of antimonial therapy than before therapy. After a six-month follow-up, the MCL patients had serum levels of TNF-α similar to those observed at the end of the therapy as well as to those of CL patients and control subjects. No significant variation in the serum levels of TNF-α was observed in CL patients throughout the study period (before, at the end of therapy and after a six-month follow-up). The possible relationship between the high TNF-α serum levels and severity of the disease is discussed.